Do others comprehensive income, profit, and equity attributable impact external audit fee? - Kusuma, Marhaendra; Luayyi, Sri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: Fair value accounting, fairness, and transparency are the basis for other comprehensive income (OCI), profit, and equity attributable. This research aims to analyze the impact of adding this information on external audit fees, considering that the content of financial reports becomes more extensive with a longer format.Design/Methodology/Approach: This study tested the influence of aggregate OCI, OCI to be reclassified, profit and equity attributable, and control variables (size, ROA, leverage, period, type of industry) on audit fees in 238 companies registered on IDX in all business sectors for the 2015-2021 period with data 1,666 observations.Research findings: Additional information on OCI, profits, and equity attributable has been proven to influence external audit fees because the inherent properties of OCI, such as the level of management subjectivity, sensitivity to externals, high volatility and exposure, as well as the complexity of the holding company reflecting the attribution value, could increase audit work and audit risk in assessing the fairness of OCI presentation and attribution.Theoretical contribution/ Originality: This study provides empirical evidence in Indonesia on how OCI disaggregation (reclassification), profit, and equity attributable affect external audit fees.Practitioner/Policy implication: For management, it can be an input in predicting the amount of audit fees, and for external auditors, it can be a consideration in determining the amount of audit fees by taking into account additional audit procedures due to OCI and profit attribution.Research limitation/Implication: The limitation of this research is that in measuring OCI reclassification, it only included the holding company, while OCI in subsidiaries and associations was not involved.